What Happens to Partners Who Issue Adverse Internal Control Opinions? - BAKKE, ASHLEIGH L.; COWLE, ELIZABETH N.; ROWE, STEPHEN P.; WILKINS, MICHAEL S. (Journal of Accounting Research, 2025)
ABSTRACT We investigate how audit firms balance the tension between professional responsibility and client service by examining changes in partner assignments following adverse internal control opinions (ICOs). We find that partners are significantly more likely to be reassigned when they issued an adverse ICO to any of their clients in the previous year. Further, partners issuing adverse ICOs experience unfavorable changes in their client portfolios in the form of lower fees and less prestigious assignments. We find that consequences are more negative when adverse ICOs are issued to clients that are more important to the local office and that there are no consequences when partners issue continuing adverse opinions to clients they have “inherited” from an original adverse ICO partner. We also find that the consequences are stronger for partners of non‐Big 4 audit firms that are likely to be more sensitive to client service considerations. The negative portfolio effects we observe persist for at least three years, and our findings are robust to restrictions involving mandatory partner rotation and adverse ICOs that lead to client loss. Overall, our results are consistent with adverse ICO partners experiencing negative consequences as audit firms respond to client service incentives in the area of internal controls over financial reporting.